1972
DOI: 10.1104/pp.49.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Malate Dehydrogenase Isoenzymes from Cotton Leaves

Abstract: Malate dehydrogenase isolated from leaves of the cotton plant (Gossypium hirsutum L.) appears in the form of several isoenzymes. Four of the isoenzymes found in cotton leaf ex- (24) in wheat, three (28) or four (21) in spinach, and in certain ornamental plants only one malate dehydrogenase enzyme has been detected (12). In cotton, at least three malate dehydrogenase isoenzymes have been reported (8, 27), but with crude extracts of cotton plants the exact number of isoenzymes could not be ascertained (27).In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1973
1973
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…On the other hand, the sequence further downstream (residues 22-32) shows a high degree of diversity among pig heart mitochondrial, E. coli and N. alba MDH enzymes. It has been shown that this particular region (residues [22][23][24][25][26][27][28][29][30][31][32] contains no significant functional domain [50]. …”
Section: Km Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the sequence further downstream (residues 22-32) shows a high degree of diversity among pig heart mitochondrial, E. coli and N. alba MDH enzymes. It has been shown that this particular region (residues [22][23][24][25][26][27][28][29][30][31][32] contains no significant functional domain [50]. …”
Section: Km Valuesmentioning
confidence: 99%
“…In crude extracts it was shown that MDH might exist as oligomeric forms with the Mr much higher than the usual 60000-70000, as indicated by non-denaturing polyacrylamide/starch-gel electrophoresis and gel-filtration column chromatography [21]. These high-Mr MDH species, usually in addition to the normal-Mr form of the enzyme, have been reported in bacteria [1,2], fungi [6], animal mitochondria [22] and, most commonly, in higher plants [21,23,24]. These results indicated that the higherMr species of MDH in higher plants might result from aggregation of low-Mr species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent work has demonstrated a further isoenzyme of malate dehydrogenase localized in plant microbodies (22,23,29). Although the isoenzymes of malate dehydrogenase in higher plant tissues have been the subject of many investigations (11,(21)(22)(23)(28)(29)(30), little is known about the distribution and function of these isoenzymes in the algal cell. When Euglena cell organelles were separated by sucrose density gradient centrifugation, malate dehydrogenase activity was recorded in several fractions (17).…”
mentioning
confidence: 99%
“…It now appears that previous studies on the aggregation behavior of MS under low-ionic-strength conditions overlooked its possible association with gMDH and that the decameric MS structure postulated by Henry et al (1992) is likely to correspond to an association between octameric MS and tetrameric gMDH. Our finding of MDH activity eluting as complexes of high Mr (670 kDa and 140 kDa) is not unusual; indeed, elution profiles of plant MDHs with apparent high-Mr values of 500kDa and 280kDa have been reported (O'Sullivan and Wedding 1972;Habig and Racusen 1974). Although the high-Mr MDH isoforms are very similar to the most commonly found low-Mr isoform with respect to optimal pH, K m for malate, and inhibition by various unreactive substrate analogs, they differ in their electrophoretic properties and ability to reduce 3-acetylpyridine-deamino-NAD + (Habig and Racusen 1974).…”
Section: Discussionmentioning
confidence: 60%